Determinación de la cultura ambiental y la responsabilidad social en la Comunidad Padre Cocha, distrito de Punchana, Iquitos - Chavez Veintemilla, Carlos Alberto (Universidad Nacional de la Amazonía Peruana, 2024)
The author of the thesis “Determination of environmental culture and social responsibility in Padre Cocha community, Punchana District, Iquitos”, investigated the residents who carry out various economic, social, and biophysical activities in the study area and also from the opinion and in situ observation of the thesis student. The quantitative approach has been used for the opinions, three indicators of the environmental culture of the residents were quantified, these are: institutionality, biophysical impact and socio economic impact. Under the qualitative approach, the following indicators were investigated: Differentiation, Prestige and Fidelity. The type of research was a mixed (quantitative-qualitative), transectional research with descriptive design. The sample was the application of 40 heads of family belonging to the community, a structured observation that was carried out by the thesis student. According to the results, the proposed hypothesis not is accepted, since greater environmental culture and compliance with the social responsibility of the different institutions such as the state-private company-NGO (social organizations) and the Academy are required for residents to improve their quality. of life.

El autor de la tesis “Determinación de la cultura ambiental y la responsabilidad social en la comunidad Padre Cocha, Distrito de Punchana, Iquitos”, investigó a los pobladores que realizan diversas actividades económicas, sociales, biofísicas del área de estudio y también desde la propia opinión y observación in situ del tesista. Se ha empleado el enfoque cuantitativo para las opiniones, fueron cuantificados tres indicadores de la cultura ambiental de los pobladores, éstos son: la institucionalidad, el impacto biofísico y el impacto socio-económico. Bajo el enfoque cualitativo se investigaron los siguientes indicadores: Diferenciación, Prestigio y Fidelidad. El tipo de investigación fue una investigación mixta (cuanti-cualitativa), transeccional con diseño descriptivo. La muestra fue la aplicación de 40 jefes de familia pertenecientes a la comunidad, una observación estructurada que fue realizada por el tesista. De acuerdo a los resultados no se acepta la hipótesis planteada, pues se requiere mayor cultura ambiental y el cumplimiento de la responsabilidad social de las diferentes instituciones como estado-empresa privada-ONG (organismos sociales) y de la Academia para que los pobladores mejoren su calidad de vida.
Keywords: Responsabilidad social; Impacto ambiental; Indicadores socioeconómicos; Comunidad local; https://purl.org/pe-repo/ocde/ford#5.02.04